Re-evaluation of Opuntia matudae (Cactaceae) - Martínez-González, César Ramiro; Gallegos-Vázquez, Clemente; Scheinvar, Leía; León, María Eugenia Muñiz-Díaz De; Jiménez-Ramírez, Jaime (Phytotaxa, 2019)
A detailed morphological and molecular study on Opuntia matudae and O. hyptiacantha is presented. These two species have been long considered to belong to the same taxon, although no investigations were carried out in depth. Moreover, no published phylogenetic study of the genus Opuntia include both species. Our data support the recognition of O. matudae and O. hyptiacantha as different and unrelated species.